INFLUENCE OF SOWING DATES AND FERTILISER APPLICATION RATES ON PHOTOSYNTHETIC POTENTIAL OF WINTER BARLEY VARIETIES - Yarkulova Zulayho Rakhimovna (Journal Park Publishing, 2024)
It was found that barley plant height decreased with delayed sowing date, resistance to lodging increased, increased with increasing fertiliser application rate, and resistance to lodging decreased. Photosynthetic potential (PP) of winter barley variety Mavlono makes from 1.155 to 2.207 million m2cут/ha on irrigated lands depending on sowing dates and fertiliser application rates, of duvarak variety Bolgali - from 1.67 to 2.273 million m2day/ha. When sown at 15.X of the growing seasons, FP changed from 1.464 million to 2.207 million m2day/ha for the variety Mavlono and from 1.426 to 2.273 million m2day/ha for the variety Bolgali, respectively. If sowing earlier or later than the optimum sowing date - 15.X. led to a decrease in FP of winter varieties Mavlono and Duvarak Bolgali, the increase in nitrogen fertilisers from 60 to 180/ha provided an increase in this indicator.
Keywords: barley, photosynthesis, Mavlono, Bolgali, fertilisation.